ISU201 Enhances the Resolution of Airway Inflammation in a Mouse Model of an Acute Exacerbation of Asthma - Yuka Hiroshima; Linda Garthwaite; Kenneth Hsu; Hyouna Yoo; Sang-Ho Park; Carolyn L. Geczy; Rakesh K. Kumar; Cristan Herbert (Mediators of Inflammation)
Glucocorticoids are commonly used for treating asthma and its exacerbations but have well-recognised adverse effects and are not always effective. Few alternative treatments exist. Using a murine model of an acute exacerbation of asthma, we assessed the ability of ISU201, a novel protein drug, to suppress the inflammatory response when administered after induction of an exacerbation. Sensitised mice were chronically challenged with a low mass concentration of aerosolised ovalbumin, and then received a single moderate-level challenge to simulate an allergen-induced exacerbation. ISU201 was administered to mice 2 and 8 hours later, while pulmonary inflammation and expression of mRNA for chemokines and proinflammatory cytokines were assessed after 4, 12, and 24 hours. Relative to vehicle-treated controls, ISU201 suppressed accumulation of pulmonary neutrophils and eosinophils, while accelerating the decline in CXCL1, TNF-α, and IL-6 in lavage fluid and lung tissue. ISU201 significantly reduced peak expression of mRNA for the chemokines Cxcl9 and Cxcl10, the adhesion molecules Icam1 and Vcam1, and the proinflammatory cytokines Il1b, Il12p40, and Csf1. The ability of ISU201 to promote resolution of inflammation suggests that it may have potential as an alternative to glucocorticoids in the management of asthma, including when administered after the onset of an acute exacerbation.